Molecular Docking Analysis of Coumarin and Indole Derivatives Targeting the MexB and GyrB in Multidrug-resistant Pseudomonas aeruginosa Clinical Isolates - Hawraa Natiq Kabroot AL-Fatlawy (Journal of Pure and Applied Microbiology, 2026)
Multidrug-resistant (MDR) Pseudomonas aeruginosa has emerged as a significant clinical threat due to its high resistance to multiple antibiotic classes and the limited effectiveness of current therapeutic options. This study aimed to evaluate selected coumarin and indole derivatives targeting the MexB and GyrB proteins of MDR P. aeruginosa using an integrated in silico approach, supported by molecular characterization of clinical isolates. A total of 44 clinical P. aeruginosa isolates recovered from sputum, urine, wound swabs, and burn swabs were examined for antimicrobial susceptibility, revealing extensive drug resistance. Complete resistance (100%) was observed against amoxicillin-clavulanic acid (AMC), cefotaxime (CTX), and trimethoprim-sulfamethoxazole (SXT). Resistance rates were 97.7% for ticarcillin-clavulanic acid (TIM), 88.63% for amikacin (AK), 60% for imipenem (IMP) and meropenem (MEM), and 52.27% for ciprofloxacin (CIP) and levofloxacin (LEV). PCR analysis confirmed the presence of the GyrB and MexB genes in all isolates. Representative PCR-positive isolates were sequenced and verified by BLAST analysis. The nucleotide sequence of the GyrB gene has been deposited in the DDBJ under accession number LC919849, and the corresponding protein sequence was assigned GenBank accession number BHR60112.1. Molecular modeling and structural validation of the GyrB and MexB proteins were performed prior to molecular docking analysis. Novobiocin and PAβN were selected as reference inhibitors for GyrB and MexB, respectively, while coumarin- and indole-based compounds were evaluated as candidate ligands. Docking analysis revealed strong predicted binding affinities for novobiocin (-10.2 kcal/mol) and PAβN (-8.1 kcal/mol). The coumarin derivative exhibited favorable predicted interactions within the ATP-binding pocket of GyrB, whereas the indole derivative demonstrated favorable predicted binding within the substrate-binding cavity of MexB. ADMET and toxicity analyses indicated favorable predicted drug-likeness for both compounds, with high gastrointestinal absorption, no bioavailability violations, and a score of 0.55. However, the indole derivative showed a positive AMES test prediction, indicating potential mutagenic liability. Molecular dynamics simulations demonstrated the structural stability of the modeled MexB protein over a 25 ns simulation period. Overall, these findings provide preliminary in silico evidence supporting further investigation of coumarin and indole derivatives as candidate compounds targeting GyrB and MexB in MDR P. aeruginosa.